Subfamily logos: visualization of sequence deviations at alignment positions with high information content - Beitz, Eric (BioMed Central, 2006)
BACKGROUND: Recognition of relevant sequence deviations can be valuable for elucidating functional differences between protein subfamilies. Interesting residues at highly conserved positions can then be mutated and experimentally analyzed. However, identification of such sites is tedious because automated approaches are scarce. RESULTS: Subfamily logos visualize subfamily-specific sequence deviations. The display is similar to classical sequence logos but extends into the negative range. Positive, upright characters correspond to residues which are characteristic for the subfamily, negative, upside-down characters to residues typical for the remaining sequences. The symbol height is adjusted to the information content of the alignment position. Residues which are conserved throughout do not appear. CONCLUSION: Subfamily logos provide an intuitive display of relevant sequence deviations. The method has proven to be valid using a set of 135 aligned aquaporin sequences in which established subfamily-specific positions were readily identified by the algorithm.